Fractionation of multicomponent sugar mixtures using a pseudo simulated moving bed - Mata, V.G. (2010)
A model for the fractionation of a ternary mixture of sugars by pseudo-simulated moving bed chromatography, according to the JO process of Japan Organo Co., is presented. This methodology is applied to the separation of a ternary mixture constituted by two sugars – sucrose (disaccharide) and fructose (monosaccharide) – and one non-sugar – betaine.